Time Series Analysis of Biophysical Variables in Four Ecoregions of Guanacaste, Costa Rica - Vega-Araya, Mauricio (2019)
In this work, the results of analyses of Leaf Area Index (LAI), Fraction of Absorbed Photosinthetically Active Radiation (fPAR), and Normalized Difference Vegetation Index (NDVI) are presented for four ecoregions in the province of Guanacaste, Costa Rica. These biophysical variables are key elements for understanding phenological processes of ecosystems under climate change. Data produced by remote sensors are currently the primary source for estimation of environmental and vegetation variables at different levels (local, regional and global), and the data used in this study come from the Moderate Resolution Imaging Spectroradiometer (MODIS). The analysis is based on the decomposition of each data series into three components: stationarity, trend and residuals. The analysis was performed using the Earth Engine platform with a time resolution of 4 days and a pixel size of 500 m. Trend curves for fPAR, LAI and NDVI were very similar for three of the ecoregions analyzed, which suggests that it will not be necessary to perform independent analysis for these variables in the future. On the other hand, the ecoregions show internal homogeneity, but heterogeneity between them; however, seasonal moist forest and Pacific dry forests have very similar maximum and minimum values in their trends. It therefore appears that the decomposition of time series into trends and stationarity is an appropriate method for monitoring change, and is also a valuable tool for relating biophysical variables and their productivity with other climatic elements, such as the ENSO effect.